Taxonomy of Oceanapia Norman, 1869 (Demospongiae: Haplosclerida: Phloeodictyidae) from the Brazilian coast - Neto, Carlos Santos; Nascimento, Elielton; Cavalcanti, Thaynã; Pinheiro, Ulisses (Zootaxa, 2018)
The genus Oceanapia Norman, 1869 comprises 95 species worldwide, 20 from the Atlantic Ocean and seven from Brazil. Oceanapia includes sponges with hollow body and numerous fistulae; spicules are oxeas or strongyles and microscleres, if present, are sigmas or toxas. Specimens were collected by trawl at Rio Grande do Norte, Pernambuco and Pará States, Brazil. Two new species are described from the Northeast Region of Brazil: Oceanapia cordia sp. nov. and Oceanapia magna sp. nov. For two preoccupied combinations, new names are proposed, Oceanapia hechteli nom. nov. and Oceanapia topsenti nom. nov. Oceanapia stalagmitica (Wiedenmayer, 1977) is recorded and described for the first time from Brazil. A taxonomic study of seven specimens of Oceanapia from the North and Northeast region (Brazil) is given, including description, illustrations and geographical distribution. The two new species are compared with all other descriptions of Oceanapia from the Atlantic Ocean.